2010
DOI: 10.1055/s-0029-1245183
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of Intravitreally Injected Ranibizumab Doses: An Experimental Study

Abstract: Under optimized laboratory conditions the use of Lucentis injection sets results in a relatively bad controlled application of ranibizumab doses. Preloading of syringes to the level of the intended injection should be abandoned and substituted by a differential injection mode. It seems recommendable to use smaller syringes than those provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Meyer et al postulier-ten außerdem, dass die unterschiedliche Häufigkeit der Augendruckanstiege in der regelrecht durchgeführten Präparation und dem Aufziehen der Medikamente in den dafür vorgesehenen Spritzen liegen kann [18]. Nur wenigen ist bekannt, dass allein die aufgedruckte Markierungslinie der nach ISO-Norm geeichten Tuberkulinspritzen eine Schwankungsbreite des Volumens von 2 % umfasst [19]. Dazu…”
Section: Therapieoptionen Und Risikobewertungunclassified
“…Meyer et al postulier-ten außerdem, dass die unterschiedliche Häufigkeit der Augendruckanstiege in der regelrecht durchgeführten Präparation und dem Aufziehen der Medikamente in den dafür vorgesehenen Spritzen liegen kann [18]. Nur wenigen ist bekannt, dass allein die aufgedruckte Markierungslinie der nach ISO-Norm geeichten Tuberkulinspritzen eine Schwankungsbreite des Volumens von 2 % umfasst [19]. Dazu…”
Section: Therapieoptionen Und Risikobewertungunclassified
“…15,16 Experimental injections on porcine eyes in this study were performed by clinicians using their normal clinical technique. The differential injection method used in our experiment has previously been found to be the most precise method for delivering the desired volume with a mean variation of less than 2%.…”
Section: Discussionmentioning
confidence: 99%
“…The differential injection method used in our experiment has previously been found to be the most precise method for delivering the desired volume with a mean variation of less than 2%. 15 …”
Section: Discussionmentioning
confidence: 99%
“…One ranibizumab PFS contains 0.165 mL of ranibizumab, ensuring that one always has adequate volume to administer a single dose of 0.05 mL. Several studies have revealed considerable variability in the accuracy and repeatability achieved with typical syringes used for intravitreal injections 3135. Most commonly used small-volume syringes tend to over deliver their target volume 33,35.…”
Section: Accuracy and Precision Of Intravitreal Ranibizumab Dosesmentioning
confidence: 99%